Terapi Gen di Era Bioteknologi Modern: Aplikasi untuk Penyakit Genetik dan Non-Genetik - Nurlia, Nurlia; Hala, Yusminah (BEST Journal (Biology Education, Sains and Technology), 2024)
The aim of this research is to explore the development of gene therapy in the era of modern biotechnology and analyze its application in the treatment of genetic and non-genetic diseases. The research uses the literature review method, which involves collecting, analyzing, and synthesizing relevant scientific sources to answer research questions. The research results obtained based on a literature approach, namely gene therapy in the era of modern biotechnology, have shown significant progress in the treatment of various genetic and non-genetic diseases. Technologies such as CRISPR-Cas9 enable high-precision DNA editing, which has been used to correct genetic mutations, while for non-genetic diseases, gene therapy has provided innovative solutions, such as engineered CAR-T cells and RNA interference (RNAi). Gene therapy still faces various challenges, including the risk of off-target mutations, the body's immune response, and ethical issues and high costs. Gene therapy, as a result of technological developments and research, is expected to be an important solution for various diseases that have been difficult to treat.